Radiography Cervical Vertebrae with Suspect Spodylosis at the Prof. Dr Chairuddin Panusunan Lubis Educational Hospital University of North Sumatra Medan - Lubis, Hotben; Pardede, Parsaoran (PT Inovasi Pratama Internasional, 2023)
The cervical vertebrae (neck bones) are vertebrae which consist of seven segments which have small segment bodies and large segment openings. Radiographic techniques are the science of studying procedures for photographing objects that are examined using X-rays. Cervical spondylosis is a common degenerative disease of the cervical spine. To show abnormalities in these organs, X-rays in the field of radiology are needed. Therefore, a radiological examination is needed to show whether there is spondylosis and its effect on the surrounding organs. with AP Axial and Lateral examination techniques. The AP Axial projection shows an image of the cervical spine from the AP position. Lateral projection shows an image of the cervical vertebrae from a lateral position, and spondylosis is clearly visible at C3 and C4. In collecting data, the author used interviews and field observations. The results of the diagnostic examination provided information about abnormalities in the cervical spine using Computer Radiography (CR), a cassette measuring 24 cm x 30 cm with a device used by Philips with a capacity of 500 mA.